Comparative safety profiles of two enrofloxacin generics after repeated intracrop administration to broilers - Ehmeza, Nasser; Elmajdoub, Abdelrazzag; Abusnina, Abdurazzag; Bennour, Emad; Giuma Elhafi, Giuma Elhafi; El-Mahmoudy, Abubakr (International Journal of Biological Research, 2016)
Clinicochemical, haematological and histopathological alterations were demonstrated in broiler chickens following repeated oral bolus administration of two different enrofloxacin generic preparations, formulated as 10% oral solutions, given at a dose regimen of 10 mg/Kg body weight for 5 consecutive days. The two tested preparations were Enrol® (Medmac®, Jordan), referred thereafter as ENRO-A; and Syvaquinol® (Syva®, Spain), which referred thereafter as ENRO-B. Eighteen broilers chickens, aging 40 days old, divided equally and randomly into three groups, have been used in the present study. ENRO-A or ENRO-B was given via intra-crop route of administration at the above-mentioned dose regimen to birds of the 2nd and the 3rd groups, respectively; where those of the 1st group were given water instead and kept as control. Blood samples were collected from all birds via the wing and metatarsal veins on the 5th day for clinicochemical and haematological examinations. Birds were then humanely sacrificed and liver, kidneys and heart were dissected out for histopathological examination. Results revealed that ENRO-A induced a significant (p<0.05) increase of the activity of alkaline phosphatase compared to ENRO-B as well as control group. Both ENRO-A and ENRO-B caused significant increases in the levels of plasma urea and creatinine concentrations compared to control (p<0.05), with higher significance in case of ENRO-A. Activity of plasma creatine kinase significantly (p<0.05) increased after ENRO-A compared to control and ENRO-B-treated groups. ENRO-A and ENRO-B significantly (p<0.05) increased blood glucose and triglyceride levels compared to that of control. Cholesterol level was increased significantly (p<0.05) only after ENRO-B repeated administration. However, other metabolic parameters showed insignificant changes. Parallel inflammatory and degenerative histopathological changes in the affected organs, except kidneys, have been observed. Nevertheless, administration of either ENRO-A or ENRO-B caused insignificant changes in hematological parameters of the treated chicken groups. Data of the present study may indicate that enrofloxacin may cause organ dysfunction in broilers during the course of therapy based on clinicochemical and histopathological reasons. The data may also indicate that the pharmaceutical technology may be a detrimental factor in safety profiles of generic products based on the differences recorded between the two tested brands.